Bacterial communities in mining soils and surrounding areas under regeneration process in a former ore mine - Fernandes, Camila Cesário [UNESP]; Kishi, Luciano Takeshi [UNESP]; Lopes, Erica Mendes [UNESP]; Omori, Wellington Pine [UNESP]; Souza, Jackson Antonio Marcondes de [UNESP]; Alves, Lucia Maria Carareto [UNESP]; Lemos, Eliana Gertrudes de Macedo [UNESP] (Springer Nature, 2018)
Human activities on the Earth's surface change the landscape of natural ecosystems. Mining practices are one of the most severe human activities, drastically altering the chemical, physical and biological properties of the soil environment. Bacterial communities in soil play an important role in the maintenance of ecological relationships. This work shows bacterial diversity, metabolic repertoire and physiological behavior in five ecosystems samples with different levels of impact. These ecosystems belong to a historical area in Iron Quadrangle, Minas Gerais, Brazil, which suffered mining activities until its total depletion without recovery since today. The results revealed Proteobacteria as the most predominant phylum followed by Acidobacteria, Verrucomicrobia, Planctomycetes, and Bacteroidetes. Soils that have not undergone anthropological actions exhibit an increase ability to degrade carbon sources. The richest soil with the high diversity was found in ecosystems that have suffered anthropogenic action. Our study shows profile of diversity inferring metabolic profile, which may elucidate the mechanisms underlying changes in community structure in situ mining sites in Brazil. Our data comes from contributing to know the bacterial diversity, relationship between these bacteria and can explore strategies for natural bioremediation in mining areas or adjacent areas under regeneration process in iron mining areas.
Keywords: Bacterial diversity; Brazilian soils; Functional diversity; Iron mine